2020
DOI: 10.1007/s10875-020-00896-2
|View full text |Cite
|
Sign up to set email alerts
|

Recovery from COVID-19 in a Child with Chronic Granulomatous Disease and T Cell Lymphopenia

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), first discovered in December 2019, has led to an ongoing, unprecedented global pandemic due to coronavirus disease 2019 (COVID-19). This novel single-stranded RNA virus infects airway epithelial and other cell types expressing surface angiotensin-converting enzyme 2, with clinical manifestations ranging from asymptomatic infection to acute respiratory distress syndrome and severe organ dysfunction [1, 2]. Symptom onset is typically between 4 to 12 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(26 citation statements)
references
References 8 publications
1
25
0
Order By: Relevance
“…A total of 459 people with PI and COVID-19 are described from 54 of the 68 studies [ 12 , 13 , 16 , [18] , [19] , [20] , [21] , 24 , 26 , 27 , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] ] (Table 2). These cases came from case reports as well as cohort studies with information available for individual patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 459 people with PI and COVID-19 are described from 54 of the 68 studies [ 12 , 13 , 16 , [18] , [19] , [20] , [21] , 24 , 26 , 27 , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] ] (Table 2). These cases came from case reports as well as cohort studies with information available for individual patients.…”
Section: Resultsmentioning
confidence: 99%
“…Supporting this, some patients with PI with autoimmune or inflammatory complications had poorer outcomes [ 19 ], and some studies have found that severe COVID-19 cases are more likely to have a greater IgG response than mild cases [ 41 ]. In contrast, the more severe outcomes seen in people with defects in the T cell and innate pathways point to the importance of these pathways in preventing severe disease [ 11 , 12 , 47 , 86 ]. These findings support the development of vaccines that better target the T cells to better protect both people with PI and the general population.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 15 other patients treated with HSCT or gene therapy were infected with SARS-CoV-2 [ 5 â–Ș , 9 â–Ș , 10 , 16 , 27 , 43 ]. Of three Wiskott–Aldrich syndrome (WAS) patients who underwent HSCT ( n = 2) or gene therapy ( n = 1), one succumbed to cytomegalovirus (CMV) encephalitis and bacterial pneumonia, while the other two survived [ 5 â–Ș , 10 ].…”
Section: Overview Of Reports Of Coronavirus Disease 2019 In Patients With Inborn Errors Of Immunitymentioning
confidence: 99%
“…Two patients who were transplanted to treat X-linked proliferative syndrome due to mutations in the gene encoding X-linked inhibitor of apoptosis protein (XIAP) died after being infected with SARS-CoV-2 post-HSCT: one was infected on day 6 post-HSCT and had a mild disease, but later succumbed to fungal infection in the context of poor engraftment, and the other died of sepsis and HLH in the context of severe graft-versus-host disease (GVHD) [ 5 â–Ș , 10 ]. One patient each was transplanted for leukocyte adhesion deficiency III, nuclear factor-kappa B (NF-ÎșB) essential modulator (NEMO) deficiency, cytotoxic T-lymphocyte associated protein 4 (CTLA4) haploinsufficiency, Chediak–Higashi syndrome, or chronic granulomatous disease (CGD), and all survived COVID-19 [ 5 â–Ș , 10 , 16 , 27 , 43 ]. Finally, the Italian IEI network reports five additional patients (a sixth with WAS is already included in the report from Meyts et al ) with unspecified IEIs treated with HSCT, gene therapy or thymus transplantation, who all survived COVID-19 [ 9 â–Ș ].…”
Section: Overview Of Reports Of Coronavirus Disease 2019 In Patients With Inborn Errors Of Immunitymentioning
confidence: 99%
See 1 more Smart Citation